2022
DOI: 10.4269/ajtmh.21-1145
|View full text |Cite
|
Sign up to set email alerts
|

Application of Urine and Copro Antigen Assays after Primary Infection and Drug Treatment in an Experimental Opisthorchiasis Animal Model

Abstract: Infection by Opisthorchis viverrini causes significant health problems, including cholangiocarcinoma (CCA); thus control and elimination of this trematode is an important strategy for the reduction of CCA. Currently, urine and copro antigen detection is more sensitive than parasitological examination of the feces for the diagnosis of opisthorchiasis. Given limitations in human studies, we used an animal model to quantify the parasite antigen profiles in urine and feces in O. viverrine–infected hamsters, and po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…Antigen detection in urine samples provides advantages not only for diagnosis of light infection but also early stage (prepatent) infections where the worms are still in the immature stage and have not reached full reproductive age. 10 Our study supports this possibility because five of 42 individuals (11.9%) had six to 18 eggs per gram of O. viverrini on day 30 of the study. Possible explanations included low worm burden or a small number of very old, degenerating worms.…”
supporting
confidence: 78%
See 1 more Smart Citation
“…Antigen detection in urine samples provides advantages not only for diagnosis of light infection but also early stage (prepatent) infections where the worms are still in the immature stage and have not reached full reproductive age. 10 Our study supports this possibility because five of 42 individuals (11.9%) had six to 18 eggs per gram of O. viverrini on day 30 of the study. Possible explanations included low worm burden or a small number of very old, degenerating worms.…”
supporting
confidence: 78%
“…Evidence from animal models also indicates that the antigen detected in urine is directly linked to the presence of adult worms in the liver. 10 Therefore, human and animal studies support the reliability of urine antigen detection to indicate active or current opisthorchiasis.…”
mentioning
confidence: 96%
“…Lastly, an animal model study showed that the antigen detected in urine as well as in feces corresponded to the presence of worms in the liver of the O . viverrini -infected hamsters [ 25 ]. Moreover, after adult worms were killed by praziquantel treatment, the antigen test became negative in hamsters with complete worm clearance and the antigen test remained positive in hamsters with incomplete worm clearance.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to adult worms, O . viverrini antigen in urine and feces may originate from juvenile worms as early as one week after infection in an opisthorchiasis-animal model [ 25 ]. Further investigation is needed to determine whether a single-worm infection can be detected using urine ELISA, as has been reported in schistosomiasis [ 30 ], since this is a critical threshold to assess the impact of parasite control and elimination programs.…”
Section: Discussionmentioning
confidence: 99%
“…A long-standing mass drug administration has resulted in most people still having light O. viverrini infection, but fecal examination methods have low diagnostic sensitivity [13]. Moreover, fecal egg examination is not able to detect prepatent infection, obstruction of eggs in the biliary tract due to chronic brosis, or blockage by adult worms following recent anthelmintic treatment [12][13][14]. Repeated stool examination is recommended to increase the reliability of faecal examination [15,16], but this further increases logistical complexity during population screening.…”
Section: Introductionmentioning
confidence: 99%